Thrombomodulin is upregulated in the kidneys of women with pre-eclampsia - Cleo C. L. van Aanhold (Nature Portfolio, 2021)
Abstract The endothelial glycoprotein thrombomodulin regulates coagulation, vascular inflammation and apoptosis. In the kidney, thrombomodulin protects the glomerular filtration barrier by eliciting crosstalk between the glomerular endothelium and podocytes. Several glomerular pathologies are characterized by a loss of glomerular thrombomodulin. In women with pre-eclampsia, serum levels of soluble thrombomodulin are increased, possibly reflecting a loss from the glomerular endothelium. We set out to investigate whether thrombomodulin expression is decreased in the kidneys of women with pre-eclampsia and rats exposed to an angiogenesis inhibitor. Thrombomodulin expression was examined using immunohistochemistry and qPCR in renal autopsy tissues collected from 11 pre-eclamptic women, 22 pregnant controls and 11 hypertensive non-pregnant women. Further, kidneys from rats treated with increasing doses of sunitinib or sunitinib in combination with endothelin receptor antagonists were studied. Glomerular thrombomodulin protein levels were increased in the kidneys of women with pre-eclampsia. In parallel, in rats exposed to sunitinib, glomerular thrombomodulin was upregulated in a dose-dependent manner, and the upregulation of glomerular thrombomodulin preceded the onset of histopathological changes. Selective ETAR blockade, but not dual ETA/BR blockade, normalised the sunitinib-induced increase in thrombomodulin expression and albuminuria. We propose that glomerular thrombomodulin expression increases at an early stage of renal damage induced by antiangiogenic conditions. The upregulation of this nephroprotective protein in glomerular endothelial cells might serve as a mechanism to protect the glomerular filtration barrier in pre-eclampsia.